Contemporary aspects on the immunopathogenesis of autoimmune diseases of the epidermal basement membrane in the dog - PAPADOGIANNAKIS (E. Ι. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ), E. I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Autoimmune diseases of the epidermal basement membrane are the result of the immune system self-activation against specific antigens of its essential structural elements. This group of skin diseases is characterized by the destruction of connecting bonds between the membrane zone and dermis, which eventually leads to the dermoepidermal separation and the formation of subepidermal vesicles and bullae. In this article, the immunopathogenesis and the clinical, histopathological and immunohistochemical features of each of these skin diseases are briefly reviewed. The autoimmune diseases of the canine epidermal basement membrane have been recently classified as bullous pemphigoid, mucous membrane pemphigoid, linear IgA dermatosis, epidermolysis bullosa acquisita and bullous systemic lupus erythematosus. Recent advances in immunopathological and molecular techniques have markedly facilitated the understanding of their pathogenesis, thus giving the opportunity for the development of new therapeutic strategies that may improve or eliminate the clinical signs.